Kedaulatan Rakyat dan Pemilihan Kepala Daerah Dalam Konteks Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Sodikin Sodikin (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: Sovereignty of the People and local elections in the Context of the Constitution of the Republic of Indonesia Year 1945. There are two opinions in the phrase